Thinking in Chinese vs. thinking in English : Social preference and risk attitudes of multicultural minds - King King Li (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This paper investigates whether language priming activates different cultural identities and norms associated with the language communicated; bilingual subjects are given Chinese instructions in the Chinese treatment and English instructions in the English treatment. The main findings are: (1) in social preference games involving strategic interactions, e.g., the trust game, subjects in the Chinese treatment are more trusting and trustworthy than in the English treatment. However, (2) in individual choice games about social preference, such as the dictator game, while there is no treatment difference, subjects exhibit in-group favoritism only in the Chinese treatment. Further, (3) subjects in the Chinese treatment expect others to be more risk seeking, and prefer to pick Chinese lucky numbers in a lottery game. These findings support the hypothesis that languages are associated with cultural frames and that communicating in a particular language increases the cognitive accessibility of norms associated with that language.
Keywords: C91; D03; D81; Z10; 330; identity; cross-cultural differences; language; bilingual; biculture; social preference; risk attitudes; Risikopräferenz; Soziale Beziehungen; Soziale Wohlfahrtsfunktion; Multikulturelle Gesellschaft; Sprache; Spieltheorie; Test